2017
DOI: 10.1038/s41523-017-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor as a mediator and biomarker of radioresistance in triple-negative breast cancer

Abstract: Increased rates of locoregional recurrence have been observed in triple-negative breast cancer despite chemotherapy and radiation therapy. Thus, approaches that combine therapies for radiosensitization in triple-negative breast cancer are critically needed. We characterized the radiation therapy response of 21 breast cancer cell lines and paired this radiation response data with high-throughput drug screen data to identify androgen receptor as a top target for radiosensitization. Our radiosensitizer screen nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 27 publications
3
55
2
Order By: Relevance
“…These data suggest that CPNE1‐high‐expressing TNBC cells are resistant to DNA‐damaging radiotherapy. Consistent with our results, other studies reported that MDA‐MB‐231 cells demonstrated a higher survival fraction than MDA‐MB‐468 cells after 2 or 4 Gy 28,29 . However, the differences in colony formation between MDA‐MB‐468 and MDA‐MB‐231 cells after 4 Gy were not significant 30 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data suggest that CPNE1‐high‐expressing TNBC cells are resistant to DNA‐damaging radiotherapy. Consistent with our results, other studies reported that MDA‐MB‐231 cells demonstrated a higher survival fraction than MDA‐MB‐468 cells after 2 or 4 Gy 28,29 . However, the differences in colony formation between MDA‐MB‐468 and MDA‐MB‐231 cells after 4 Gy were not significant 30 .…”
Section: Discussionsupporting
confidence: 91%
“…MDA-MB-468 cells after 2 or 4 Gy. 28,29 However, the differences in colony formation between MDA-MB-468 and MDA-MB-231 cells after 4 Gy were not significant. 30 It was recently reported that PI3K/ AKT inhibitor inhibited the resistance to endocrine or DNA-damaging radiotherapy in ER-positive early patients with BC.…”
Section: Mda-mb-231 Cells Demonstrated a Higher Survival Fraction Thanmentioning
confidence: 87%
“…These results establish DYRK2 protein levels as potential prognostic factor and promissing novel therapeutic target in TNBC, especially in the TN/AR-negative subgroup of patients, for whom there is no targeted therapy available. Interestingly, several of the commonly used TNBC cell models (including the two cell lines used in this study, MDA-MB-231 and MDA-MB-468) are also AR negative 23 , and thus there is full agreement between our cell culture and tissue analysis data.…”
Section: -Dyrk2 Levels Correlate With Hsf1 Nuclear Levels and Assocsupporting
confidence: 61%
“…Beyond the role of the androgen receptor in driving cancer cell proliferation, previous work in prostate cancer and breast cancer has demonstrated the role of AR in mediating DNA repair and in the DNA damage response following radiation therapy (26)(27)(28)(29). These studies suggest that pharmacologic abrogation of AR both in prostate cancer (darolutamide and enzalutamide) and in AR+ TNBC (enzalutamide) may be a viable treatment strategy for the radiosensitization of aggressive tumors, as AR inhibition may inhibit DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that pharmacologic abrogation of AR both in prostate cancer (darolutamide and enzalutamide) and in AR+ TNBC (enzalutamide) may be a viable treatment strategy for the radiosensitization of aggressive tumors, as AR inhibition may inhibit DNA repair. In addition, following radiation, AR activity increases the expression and phosphorylation of DNAPKcs (26,28). Therefore, AR inhibition may render cells more sensitive to radiation treatment by reducing activity of DNAPKcs and inhibiting non-homologous end joining (NHEJ), but not homologous recombination (HR) (27).…”
Section: Introductionmentioning
confidence: 99%